141 Tissue factor pathway inhibitor regulates vascular development in zebrafish. (9th June 2011) - Holroyd, E W; Pierret, C K; Bedell, V M; Townend, J; Ekker, S C; Simari, R D
Abstract : Introduction: Angiogenesis requires the coordinate regulation of multiple biological pathways, including haemostasis. Tissue factor pathway inhibitor (TFPI) is a potent anticoagulant molecule, inhibiting tissue factor-led coagulation. However, the role of TFPI in vascular development is unknown. Zebrafish (Danio rerio) provide a unique model system to study vascular development in vertebrates. Despite the divergence of jawed fish (teleosts) over 430 million years ago, there is notable conservation of the constituent molecules of the clotting cascade. Multiple features make this vertebrate model unique, including its genetic accessibility, the ability to titrate the degree of genetic knock-down, external embryonic development, and the transparent nature of the embryos. Methods: Using in-situ hybridisation techniques, we demonstrate TFPI expression during early vertebrate development. We then utilise transgenic fish with labelled endothelium (Fli1GFP) and erythrocytes (GATA1dsRed), to study in real time, concomitant fluorescent imaging of both structural development and dynamic blood flow observation, in living zebrafish embryos. Results: TFPI expression was identified at 24 h post fertilisation (hpf) in the pronephros (Abstract 141 figure 1 —dark blue staining denotes TFPI expression; none seen in control embryos). Subsequently, TFPI mRNA became more abundant, localising to developing kidney, gut, and vasculature. Morpholino (MO)-based knockdown of TFPI resulted in coagulopathy and disordered vascular development (Abstract 141 figure 2 . left column: green endothelial Fli1GFP, right column: red erythrocytes. AB: uninjected controls. CD: MO controls. E–P: TFPI knockdown). Abnormally targetted (ie, vessels sprouting from normal site but growing in abnormal direction; grey arrows) and extra vessels (ie, superfluous vessels not seen in controls; white arrows in Abstract 141 figure 2EFHIK&L ) were seen by 48hpf. TFPI MO induced coagulopathy (a spontaneous clot or bleed; white arrows Abstract 141 figure 2GJMP ) in 25.2±2.3% (p<0.01 cf. uninjected controls) at 3 ng and 23.8±5.8% (p<0.01) at 9 ng. Control embryos did not demonstrate significant signs of coagulopathy (3.3±3.3%). Extra arteries occurred in 26.4±2.6% (p<0.001 by ANOVA cf. uninjected controls) of embryos injected with 3 ng of TFPI MO. To further define the role of TFPI in vascular function, RNAi-mediated knockdown of TFPI was performed in human endothelial cells (EC). Knockdown of TFPI resulted in enhanced EC tube formation on Matrigel and EC migration in injury model associated with increased phosphorylation of Vascular Endothelial Growth Factor Receptor-2. Conclusion: These data represent the first demonstration of TFPI expression in zebrafish and the first description of a unique phenotype following TFPI knockdown. They support a model in which TFPI acts a molecular break to angiogenesis both in vivo, during early vertebrate embryogenesis, and in vitro in mature human endothelial cells, secondary to constitutive regulation of VEGF signalling.